Whole-genome sequencing to uncover sources of carbapenemase gene transmission evading standard-of-care infection prevention measures - Ng, Oon Tek (Nanyang Technological University, 2024)
Carbapenemase-producing Enterobacterales (CPE), with extremely limited safe treatment options, are an increasing threat to human health related to rapid international spread and increased morbidity and mortality. Whole-genome sequencing has revolutionised the ability to track transmission of CPE. CPE genomic dissemination can be divided into two main modes, namely clonal-linked transmission, and plasmid-linked transmission. Epidemiologically, available data also suggests that in addition to person-to-person transmission, the inanimate environment, especially the wet environment plays a key role as a reservoir of carbapenemase genes. To better understand the hospital transmission of CPE, combined genomic-epidemiologic analysis of 1215 whole-genome sequenced CPE isolates collected over a 4.7-year period from all multi-disciplinary hospitals in Singapore was conducted. In the introduction, the discovery and dissemination of carbapenemase genes, common whole-genome sequencing platforms and analysis tools and published sources of CPE in the healthcare environment are discussed. Additionally, an initial pilot project establishing the capacity within the Carbapenemase-producing Enterobacterales in Singapore (CaPES) network for determination of CPE transmission across four hospitals is reviewed. The current thesis focuses on the findings of the combined genomic-epidemiologic analysis across a 4.7-year period. Of 779 patients (with 1215 isolates) who acquired CPE, clonal-linked transmission accounted for 42%, plasmid-linked transmission accounted for 44.8% with an additional 13.2% unable to be classified genomically. Overall CPE transmission did not decline over the study period. However sub-analysis revealed that clonal-linked transmission, especially clonal-linked transmission associated with ward direct contact, declined in the later part of the study, possibly related to the intensification of infection prevention measures. While clonal-linked transmission was associated with hospital-related contact factors (ward direct, ward indirect, hospital direct and hospital indirect), plasmid-linked transmission did not demonstrate statistically significant association with hospital-related contact factors. The findings suggest that plasmid-linked transmission accounted for a significant prevalence of carbapenemase gene transmission, epidemiologic characteristics of clonal-linked transmission and plasmid-linked transmission are different, and commonly practiced infection prevention measures in Singapore hospitals at time of study affect mainly clonal-linked transmission related to ward direct contact. Following successful completion of the primary Ph. D work, ongoing work involving more in-depth study of closed CPE plasmids is presented.